Effect of leaf type on browse selection by free ranging goats in a southern African savanna - Nyamukanza, Casper C.; Sebata, Allan (Public Library of Science, 2021)
Broad- and fine-leaved woody species respond to seasonal changes from wet to dry season differently. For example, broad-leaved species shed their leaves earlier, while fine-leaved species, especially acacias retain green foliage well into the dry season. These differences are expected to result in variation in selection of broad- and fine-leaved woody species as browse by free-ranging goats. We tested the hypothesis that free-ranging goats select broad-leaved woody species more than fine-leaved species during wet (growth) season and fine-leaved woody species more than broad-leaved species during dry season. In addition, we tested if broad- and fine-leaved woody species had different foliar dry matter digestibility and chemical composition (crude protein, neutral detergent fibre, acid detergent fibre, total phenolics and condensed tannins concentration). Free-ranging goats were observed foraging on broad- and fine-leaved woody species over a two-year period (2014 and 2015) during three seasons: early wet (October/November), late wet (February/March) and dry (May/June). Ivlev’s selectivity or Jacob’s index (Ei) was calculated for five woody species (two broad-leaved and three fine-leaved) browsed by goats during wet and dry season. Jacob’s selectivity index was higher for broad–leaved (Ziziphus mucronata and Searsia (Rhus) tenuinervis) than fine-leaved woody species (Acacia nilotica, Acacia karroo and Dichrostachys cinerea) during wet season. However, the trend was reversed during dry season with fine-leaved species having higher Jacob’s selectivity index than broad-leaved species. Leaf dry matter digestibility and chemical composition was similar between broad- and fine-leaved woody species throughout the year. We conclude that goats selected broad-leaved woody species during wet season when browse was plentiful and then switched to fine-leaved species which retained leaves during dry season.